Analisis potensi pembayaran non tunai pada pedagang di Kota Langsa - Nurjanah Nurjanah (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2021)
The study aims to look at the potential and barriers to non-cash payments in Langsa City. Using qualitative methods and the number of respondents as many as 6 people. The results of this study show that the city of Langsa has great potential in the application of non-cash payments along with the rapid increase of merchant development in the city of Langsa, and in the application has several obstacles including frequent network errors, lack of socialization about the use of digital transactions